Detection of recombinant erythropoietin biosimilar Jimaixin™ after administration in healthy subjects. Issue 1 (2nd September 2021) - Martin, Laurent; Kafi, Rafik; Zhou, Xinmiao; Zhang, Lisi; Ericsson, Magnus; Marchand, Alexandre
Abstract: Jimaixin™ (Jintan Ltd, China) is a biosimilar of recombinant erythropoietin (rEPO) now authorized for therapeutic application in China. With a risk of abuse by athletes, a clear evaluation of its detection using the electrophoretic methods in use in antidoping laboratories was necessary. In a previous work, we showed that Jimaixin™ electrophoretic profile presented slight changes compared with the original drug (first generation rEPO) and that a spike of Jimaixin™ in urine and serum was well identified by SDS‐PAGE but with less performance by IEF‐PAGE unless a neuraminidase treatment was applied first. The aims of this research were to perform an intravenous administration of Jimaixin™ on three healthy subjects (one microdose [10 IU/kg] and three therapeutic doses [50 IU/kg]) and to evaluate the detection in urine and blood up to 7 days post administration. Analysis of the samples showed that Jimaixin™ detection was complicated by IEF‐PAGE due to the loss of the most distinctive basic isoforms. In addition, a neuraminidase treatment did not improve detection (contrary to the observations from spike experiments). On the contrary, Jimaixin™ was very efficiently detected in blood and urine by SDS‐PAGE: up to 40 h after a microdose and up to 7 days after the therapeutic doses. The effect of Jimaixin™ on hematological parameters was limited to a clear but transitory increase of the reticulocytes. These data give new elements to better survey a potential misuse of Jimaixin™ by athletes. Abstract : Administration of Jimaixin was performed in healthy volunteers. Best window of detection was obtained with urine and SDS‐PAGE. Jimaixin profile by IEF‐PAGE was slightly different from the standard. Jimaixin increased RET% but not HGB in the time course of the study.